THE RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDES, AND PERCEIVED RISKS RELATED TO DIABETES MELLITUS IN ADOLESCENTS - Christine Handayani Siburian; Sammy Lazuardi Ginanjar; Tajudin; Ashar Abilowo; Abdul Kadir Hasan; Nurhayati (Universitas Kadiri, 2026)
Diabetes Mellitus is a chronic metabolic disease characterized by prolonged elevated blood glucose levels that can lead to organ damage. Many adolescents have a diet high in sugar, fast food, and sugary drinks, as well as a lack of physical activity due to gadget use and a sedentary lifestyle. These habits can lead to obesity and insulin resistance, which are major factors in the development of diabetes. The problem is worsened by limited adolescent knowledge regarding the definition, risk factors, symptoms, and prevention of diabetes mellitus. Attitudes and perceived risks related to diabetes, including the importance of physical activity, treatment, prevention of complications, and risk control, also remain low. Therefore, assessing adolescents’ knowledge and attitudes about diabetes mellitus is essential. This study aims to determine the relationship between knowledge and attitudes and perceived risks related to diabetes mellitus among adolescents. The study used a quantitative method with a cross-sectional design. The population consisted of adolescents at SMAN 4 Kota Pangkalpinang, with a sample of 277 respondents selected through simple random sampling. The instruments used were a knowledge questionnaire and an attitudes and perceived risk questionnaire. Data were analyzed using the Spearman Rho test. The results showed a significant relationship between knowledge and attitudes and perceived risks related to diabetes mellitus (p value 0.00, r 0,405). The study recommends providing health education for adolescents to improve their understanding of diabetes mellitus.